Legal Analysis of Alleged Defamation Through Social Media Causing Harm to Others (Study of Central Jakarta District Court Decision Number 589/Pid.Sus/2024/PN Jkt.Pst) - Hestu Purwestri Kusumaningtyas; Abunawas, Abunawas; Jamiatur Robekha (Jurnal Info Sains : Informatika dan Sains, 2025)
One form of unlawful acts that often occur in the development of technology and information in this digital era, is defamation or insults committed through social media. Defamation through social media is included in the category of cyber criminal acts regulated in Article 27 paragraph (3) of the ITE Law which reads: "every person deliberately and without the right distributes and/or makes accessible electronic information and/or electronic documents that have insulting and/or defamatory content. The formulation of the problem discussed is: 1) How to regulate alleged defamation through social media? and 2) How is the application of criminal sanctions against perpetrators of criminal acts that are proven to be defamatory through social media that cause harm to others?. The research method used is the normative juridical method, namely research that prioritizes literature data, namely research on secondary data. The secondary data can be in the form of primary, secondary or tertiary legal materials. Based on the results of the research, the author concludes that the application of criminal sanctions against perpetrators of criminal acts that are proven to be defamatory through social media that causes harm to others, is regulated in the ITE Law and the Criminal Code. Perpetrators can be subject to imprisonment and fines, with heavier penalties if carried out through social media because of its wider and fast-spreading impact. Defamation through social media is included in cyber crimes and is regulated in Article 27 paragraph (3) of the ITE Law which reads: "Every person deliberately and without the right to distribute and/or transmit and/or make accessible Electronic Information and/or Electronic Documents that have insulting and/or defamatory content. However, in the decision of the Central Jakarta District Court Number 589/Pid.Sus/2024/PN Jkt.Pst, the defendant was declared not legally and convincingly proven guilty of committing the criminal act as charged, thus acquitting the Defendant therefore from all charges of the Public Prosecutor.